Soil greenhouse gases fluxes from maize production under different management practices in semi-arid parts of Eastern Kenya - Macharia, Joseph M. (2017)
The Climate Food and Farming (CLIFF) Research Network is an international research network that helps to expand young researchers' knowledge and experience working on climate change mitigation in smallholder farming. CLIFF provides grants for selected doctoral students to work with CGIAR researchers affiliated with the Standard Assessment of Mitigation Potential and Livelihoods in Smallholder Systems (SAMPLES) project. This presentation is Soil greenhouse gases fluxes from maize production under different management practices in semi-arid parts of Eastern Kenya by Joseph Macharia, a CLIFF student with CCAFS Low Emission Development.